Design method of innovative box connections for modular steel constructions. (1st October 2022) - Qin, Jiajun; Tan, Ping
Abstract: Modular steel constructions (MSCs) are assembled on-site using modular units (modules) which are prefabricated in the factory. Their use offers advantages, such as superior quality of modules, less demand for laborers, less cost, high assembly efficiency, and significantly reduced waste discharge. An architecturally pleasing bolted connection named box connections (BCs) with innovative box-connecting component (BCC) was put forward in this paper to achieve vertical connection. The design method of BCs which involves determining the cross-sections of floor and ceiling beams and the design of vertical connection were also proposed to attain main mechanical properties as traditional connections (TCs). Finite element analysis and theoretical studies were conducted to verify the applicability of BCs and the correctness of the proposed design method. The results of finite element model of BCs are in good agreement with the theoretical values of lateral initial stiffness and the error is within 10%. This approach can achieve equal initial stiffness similar to that of TCs, and the lateral strength of BCs is consistently greater than that of the corresponding TCs throughout loading. The results of an finite element model of BC under cyclic load on column end showed that, the average initial stiffness values and the average ductility factors were excellent than those of TCs, and the average energy dissipation capacity values were a little worse than those of the TCs. Highlights: An innovative box connection for modular steel construction was proposed. The proposed connection can be completed only by high-strength bolts meanwhile works well with building function. Mechanical model of box connection at corner was obtained. Design of box connection was recommended. Elaborate finite element model of eight traditional connections and twenty four box connections were investigated.